2022
DOI: 10.1021/acssuschemeng.2c01959
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal Plasma-Assisted Deconstruction of High-Density Polyethylene to Hydrogen and Light Hydrocarbons over Hollow ZSM-5 Microspheres

Abstract: Non-thermal catalytic plasma has unfolded novel routes for a circular economy, providing a powerful cost-effective alternative to produce valued-added fuels from plastic waste. In this work, non-thermal plasma-assisted deconstruction of high-density polyethylene (HDPE) over a ZSM-5 catalyst with different morphologies, i.e., microspheres and nanoparticles, is reported. Deconstruction of HDPE over thermal routes is presented to benchmark the plasma pathways. Experimental data revealed that the highest yield/sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…They reported an increase of all gas yields including CO, CO 2 , CH 4 , C 2 –C 3 , and H 2 with an increase of plasma input power from 0 to 15 W. Increasing input power to 70 W led to more gas production. Nguyen et al confirmed that introducing a nonthermal-plasma stage to the thermal stage outperformed the thermal case, which can be attributed to the presence of vibrationally excited species. Increasing the input power raised the production of hydrogen and methane, which were the predominant components at higher input powers (40–60 W).…”
Section: Resultsmentioning
confidence: 99%
“…They reported an increase of all gas yields including CO, CO 2 , CH 4 , C 2 –C 3 , and H 2 with an increase of plasma input power from 0 to 15 W. Increasing input power to 70 W led to more gas production. Nguyen et al confirmed that introducing a nonthermal-plasma stage to the thermal stage outperformed the thermal case, which can be attributed to the presence of vibrationally excited species. Increasing the input power raised the production of hydrogen and methane, which were the predominant components at higher input powers (40–60 W).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of impurities and contaminants in the heavy oil feedstock may lead to electrode fouling and decreased plasma efficiency, necessitating frequent cleaning and maintenance procedures. Despite these challenges, we are convinced that the DBD plasma method remains a viable option for in‐liquid plasma fuel production from heavy carbons, particularly due to its potential for effective large‐scale operation, high flexibility for catalyst integrations, and its adaptability to various industrial settings [46] …”
Section: In‐plasma Discharge For Catalytic Heavy Oil Upgradingmentioning
confidence: 99%
“…Previous works have explored the plasma catalytic decomposition of HDPE with nonthermal atmospheric DBD plasma when employing an acid catalyst HZSM-5 zeolite, which favored the formation of light or gaseous hydrocarbons. 51 This motivated us to pursue the understanding of the product formation in a more homogeneous plasma environment (radio frequency plasma) using a greenhouse gas (GHG) CO 2 , a mild oxidant, by exploring various alkaline earth metal perovskites (MgTiO 3 , CaTiO 3 , SrTiO 3 , BaTiO 3 ) as plasma enhancers. The main driving force behind using the presented materials is the absence of acid sites, which has been shown to produce high yields of liquid hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%